Analisis Kebijakan OJK dalam Mendorong Intermediasi dan Pemulihan Ekonomi - Dyah Paramita; Lira Fadia Rahma; Endang Kartini Panggiarti (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2023)
OJK is an institution that can later carry out supervision and management of the financial sector in Indonesia. The financial sector itself will be driven by two financial institutions, one of which still dominates the financial sector, namely public banking in Indonesia. The issues that will be discussed in this article are what are the policies issued by the OJK in encouraging intermediation and economic recovery?, and how are OJK policies related to improving intermediation performance in supporting economic recovery? This article aims to find out the policies issued by OJK in encouraging intermediation and economic recovery, and to find out OJK policies regarding improving intermediation performance in supporting economic recovery. In this article, the author will use a qualitative descriptive method with a literature review approach. Based on the literature reviews that have been obtained by researchers, on average previous research has found that one of the OJK policies that can encourage economic recovery is the credit restructuring policy. In addition to the credit restructuring policy, OJK also issued several policies to encourage economic recovery in Indonesia, namely policies to maintain real sector business fundamentals, follow-up stimulus policies, and policy synergies for economic recovery.